Analisis Faktor yang Mempengaruhi Angka Melek Huruf di Indonesia Dengan Regresi Robust - Pratiwi, Indy; Triono, Wira; Panjaitan, Rizky Rafiza; Rambe, Risa Rozzaqi; Dalimunthe, Syairal Fahmy (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the factors that affect literacy rates in Indonesia using a robust regression approach. The data used included data from 34 provinces, focusing on the dependent variables, namely the literacy rate and the independent variables, namely the average length of schooling, the number of teachers, out-of-school children, PDRB per capita, and the number of poor people. The results of the analysis show the equation Y ?=97.7766-0.41220PCA1-0.2886PCA2-0.000002x_4. where PCA1 = a combination of X1 and X2 and PCA2 = a combination of X2 and X5. Every 1 unit increase in PCA1 will reduce the literacy rate by about 0.4120 or 41.2%, an increase of 1 unit of PCA2 will reduce the literacy rate by about 0.2886 or 28.86%, while in x_4 it only affects about 0.00022%. The number of children who do not attend school, children who drop out of school and the number of poor people can significantly increase the illiteracy rate. Efforts that can be made by the government are to facilitate education so that all groups can access education and educate the public that education is very important and will be the foundation of the nation and state in the future..